2020
DOI: 10.1017/dmp.2020.13
|View full text |Cite
|
Sign up to set email alerts
|

Tools for Assessment of Country Preparedness for Public Health Emergencies: A Critical Review

Abstract: Recent international communicable disease crises have highlighted the need for countries to assure their preparedness to respond effectively to public health emergencies. The objective of this study was to critically review existing tools to support a country’s assessment of its health emergency preparedness. We developed a framework to analyze the expected effectiveness and utility of these tools. Through mixed search strategies, we identified 12 tools with relevance to public health emergencies. There was co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 11 publications
0
11
0
Order By: Relevance
“…To better identify the advantages and gaps and summarise the lessons learnt, there will be an analysis based on the proposed preliminary evaluation framework ( table 4 ) after the data presentation. This framework is amended from Haeberer et al ’s framework 22 according to the topic of this scoping review and the contents relying on the authors’ subjective judgement were cut. The purpose of this framework is not to set criteria for the indices or assessment tools.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…To better identify the advantages and gaps and summarise the lessons learnt, there will be an analysis based on the proposed preliminary evaluation framework ( table 4 ) after the data presentation. This framework is amended from Haeberer et al ’s framework 22 according to the topic of this scoping review and the contents relying on the authors’ subjective judgement were cut. The purpose of this framework is not to set criteria for the indices or assessment tools.…”
Section: Methodsmentioning
confidence: 99%
“…Some reviews have included indices or assessment tools applied in regions like Europe as part of eligible literature. [21][22][23] Moreover, considering the objectives of this scoping review, including indices or assessment tools applied in particular countries or regions will weaken the global generalisability. In addition, since the concept of 'governance' in this scoping review involves diverse actors and organisations, governance of only one type of organisation (eg, hospital or enterprise) does not fit this research's scope.…”
Section: Eligible Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…However, the IHR and JEE scarcely mention recovery. Recent reviews of major global health security initiatives ( Carlin et al, 2019 ), high-level recommendations on national preparedness for public health emergencies ( WHO, 2019 ), and tools for countries to monitor PHEP capabilities ( Haeberer et al, 2020 ) all identify epidemic recovery as a persistent gap.…”
Section: Introductionmentioning
confidence: 99%
“…Despite attempts to develop preparedness measures, there remains a lack of consensus and, consequently, a research gap about how preparedness evaluation should be done (Savoia et al 2017, Belfroid et al 2020, Haeberer et al 2020, Asch and co-authors (2005 concluded that existing tools lacked objectivity and scientific evidence, an issue that persists. Objective evaluation would allow for intersubjective comparability of preparedness.…”
Section: Introductionmentioning
confidence: 99%